2018
DOI: 10.2340/16501977-2308
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ultrasound-guided vs direct approach corticosteroid injections for carpal tunnel syndrome: A double-blind randomized controlled trial

Abstract: Both ultrasound-guided and direct approach corticosteroid injection protocols improved clinical symptoms and signs, physical function, and most electrodiagnostic parameters of patients with carpal tunnel syndrome throughout the follow-up period. However, the ultrasound-guided injection group showed greater improvements in the Semmes-Weinstein Monofilament test, sensory nerve conduction velocity, and digit-4 comparison study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 31 publications
(56 reference statements)
1
35
0
Order By: Relevance
“…Although LCIs are considered in most patients with mild-to-moderate CTS 14 , our findings showed that patients who refuse surgical intervention may benefit from the injection. A number of randomized controlled trials have documented the treatment efficacy of LCI in patients with mild and moderate CTS 7,10,15 . We found that improvement of mean pain severity, symptoms and functional status scores did not differ between mild, moderate and severe CTS patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LCIs are considered in most patients with mild-to-moderate CTS 14 , our findings showed that patients who refuse surgical intervention may benefit from the injection. A number of randomized controlled trials have documented the treatment efficacy of LCI in patients with mild and moderate CTS 7,10,15 . We found that improvement of mean pain severity, symptoms and functional status scores did not differ between mild, moderate and severe CTS patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 weeks, they found that there was no significant difference in symptom severity scores between the out-plane ultrasound-guided injection and direct injection groups 19 . In a double blind randomized controlled trial, Chen et al assessed the effectiveness of ultrasound-guided versus direct-approach injections for CTS 15 . They reported that they did not observe any difference in the clinical evaluation of the outcomes of the two groups, similar to the findings of Lee et al Ulnar approaches between the palmaris longus and flexor carpi radialis tendons, or just medial to the palmaris longus tendon, have commonly been performed as a successful blind injection technique for CTS treatment [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Although corticosteroid injections are a mainstay of conservative CTS treatment, they have been found to be inferior to surgery in the long term . Multiple recent studies, including a meta‐analysis, have demonstrated that injections performed with US guidance can be more efficacious than those without . In‐plane transverse median nerve injections can be performed from either a radial (lateral) or an ulnar (medial) approach .…”
Section: Approach To Ultrasound‐guided Treatment Of Individual Entrapmentioning
confidence: 99%
“…37 Multiple recent studies, including a meta-analysis, have demonstrated that injections performed with US guidance can be more efficacious than those without. [38][39][40][41][42] In-plane transverse median nerve injections can be performed from either a radial (lateral) or an ulnar (medial) approach. 43 The advantage of the ulnar approach is that it avoids most tendons and the palmar cutaneous nerve, whereas the radial approach has the advantage of avoiding the ulnar artery.…”
Section: Fibular (Peroneal) Nerve At the Fibular Neck Neuropathymentioning
confidence: 99%
“…9 There are different methods to treat CTS, including medication, 10 splint, exercises, 11 surgery, 12 low-level laser therapy (LLLT), [13][14][15] Bioptron, 16 and ultrasound. 17 Among various therapies, the LLLT and ultrasound methods may have potential effects on inducing biophysical effects within tissues. 18,19 The experiments on nerve regeneration and neurotransmission, which are affected by LLLT 20,21 and ultrasound 22,23 stimulatory effect, suggest that these treatments may facilitate the recovery process in the compressed nerve.…”
Section: Introductionmentioning
confidence: 99%